Language aptitude in the visuospatial modality: L2 British Sign Language acquisition and cognitive skills in British Sign Language-English interpreting students - Watkins, Freya; Webb, Stacey; Stone, Christopher; Thompson, Robin L. (Frontiers in Psychology, 2022)
Sign language interpreting (SLI) is a cognitively challenging task performed mostly by second language learners (i.e., not raised using a sign language as a home language). SLI students must first gain language fluency in a new visuospatial modality and then move between spoken and signed modalities as they interpret. As a result, many students plateau before reaching working fluency and training program drop-out rates are high. However, we know little about the requisite skills to become a successful interpreter: the few existing studies investigating SLI aptitude in terms of linguistic and cognitive skills lack baseline measures. Here we report a three-year exploratory longitudinal skills assessments study with British Sign Language-English SLI students at two universities (n=33). Our aims were two-fold: first to better understand the prerequisite skills that lead to successful SLI outcomes; second to better understand how signing and interpreting skills impact other aspects of cognition. A battery of tasks was completed at four time points to assess skills including but not limited to: multimodal and unimodal working memory, 2-dimensional and 3-dimensional mental rotation and English comprehension. Dependent measures were BSL and SLI course grades, BSL reproduction tests and consecutive SLI tasks. Results reveal that initial BSL proficiency and 2D mental rotation were associated with selection for the degree program, while visuospatial working memory was linked to continuing with the program. 3D mental rotation improved over the course of the degree, alongside some limited gains in auditory, visuospatial and multimodal working memory tasks. Visuospatial working memory and mental rotation were the skills closest associated with BSL and SLI outcomes, in particular those tasks involving sign language production, thus highlighting the importance of cognition related to the visuospatial modality. These preliminary data will inform SLI training programs from applicant selection through to curriculum design.